2021
DOI: 10.1371/journal.pone.0246940
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and sleep quality among adolescents in a peri-urban setting in Nepal: A cross-sectional school-based survey

Abstract: Background Excessive use of the internet among adolescents often led to later bedtimes and poor sleep quality. This study assessed the relationship between internet addiction and sleep quality among adolescents in a peri-urban setting in Nepal. Method This cross-sectional study employed a questionnaire survey among 390 adolescent students recruited from two schools in Kirtipur Municipality in Nepal. The Internet Addiction Test and the Pittsburgh Sleep Quality Index were used to assess internet addiction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
2
11
1
1
Order By: Relevance
“…26 and Mercer PW et al (1998), reported that 63% of the adolescents had poor sleep quality. 25 These findings were discordant with the previous research because the present study data were collected right after the lockdown period. They had sufficient leisure time at home.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…26 and Mercer PW et al (1998), reported that 63% of the adolescents had poor sleep quality. 25 These findings were discordant with the previous research because the present study data were collected right after the lockdown period. They had sufficient leisure time at home.…”
Section: Discussionsupporting
confidence: 78%
“…This finding was a mismatch with the research conducted by Karia SB et al (2021), showed that 40% of science students and 33% of commerce students experienced no clinically significant insomnia, respectively. 24 Another survey conducted by Karki K et al (2021) highlighted that poor sleep quality was found among 31% . 25 A dissimilar findings were reported by An J et al(2014), that 26.7% of the adolescents had poor quality of sleep .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed the prevalence of poor sleep quality among undergraduate medical students (38.2%), which is higher than the study reported among undergraduate non-medical PLOS GLOBAL PUBLIC HEALTH students (35.4%) [19] and school level students (31%) in Nepal [27]. A similar study from a private medical college of Nepal showed a higher proportion of poor sleep quality (44.3%) than our study [17].…”
Section: Discussioncontrasting
confidence: 75%
“…Problematic use of smartphones has been attributed to time displacement, such as smartphone use that transcends to delay in bedtime due to surfing the content of the media, causing arousal and interfering with the ability to fall asleep. Additionally, it has a biological impact through light emission of the device in the blue spectrum resulting in melatonin suppression which further leads to difficulty in sleep initiation and non-restorative sleep [ 6 – 8 , 16 , 17 , 19 ]. With the advancement of technology and the use of smartphones, the sleep problem has become a growing concern.…”
Section: Introductionmentioning
confidence: 99%